Analysis of the Effect of Bank Soundness and Macroeconomics on Financial Distress in Conventional Commercial Banks - Atika Jauharia Hatta Hambali; Safira Putri Emilia; Junaidi Junaidi (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2021)
This research aims to analyze the effect of bank soundness and macroeconomics on the financial distress of conventional banking in Indonesia in the 2015-2019 period. The bank soundness is measured using the Risk-Based Bank Rating or RGEC method which is proxied by the ratio of non-performing loan (NPL), size of board directors, return on asset (ROA), capital adequacy ratio (CAR). The macroeconomic variable was measured using exchange rate while the dependent variable was measured by Altman Z-Score modification. The population of this research is all conventional banking companies listed on the Indonesian Stock Exchange in 2015-2019. The method used for selecting the sample is purposive sampling. The sample obtained was 37 banks with a five years observation period. This research is using multiple linear regression analysis. The result of this research indicates that the size of the board direction, return on asset, and capital adequacy ratio harms the financial distress of conventional banking in Indonesia in the 2015-2019 period. While the non-performing loan and exchange rate do not affect the financial distress of conventional banking in Indonesia in the 2015-2019 period.